2017
DOI: 10.1097/cad.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin disrupts androgen responsiveness of human prostate cancer cells by stimulating the 26S proteasome-mediated degradation of the androgen receptor protein

Abstract: Androgen receptor (AR) expression and activity is highly linked to the development and progression of prostate cancer and is a target of therapeutic strategies for this disease. We investigated whether the antimalarial drug artemisinin, which is a sesquiterpene lactone isolated from the sweet wormwood plant Artemisia annua, could alter AR expression and responsiveness in cultured human prostate cancer cell lines. Artemisinin treatment induced the 26S proteasome-mediated degradation of the receptor protein, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Short pretreatment period of artemisinin may be insufficient and does not take effect (Zheng et al, 2016 ). Second, the dose which was used in our study to activate Akt enzymatic activity is much lower than preview study (Steely et al, 2017 ). Third, dihydroartemisinin is the active metabolite of all artemisinin compounds (Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 78%
“…Short pretreatment period of artemisinin may be insufficient and does not take effect (Zheng et al, 2016 ). Second, the dose which was used in our study to activate Akt enzymatic activity is much lower than preview study (Steely et al, 2017 ). Third, dihydroartemisinin is the active metabolite of all artemisinin compounds (Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 78%
“…It is one of the most effective anti-malarial drug which has saved the lives of millions of malaria patients worldwide [10,11]. In addition to anti-malarial benefits, artemisinin has many other biological and pharmacological properties, including antioxidant, anti-inflammatory, antiviral and anti-tumor effects [12,13,14]. In addition, we have recently shown that artemisinin have neuroprotective potential [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It selectively induced the ubiquitin-26S proteasome-mediated degradation of androgen receptor (AR) without altering receptor transcript levels in androgen-responsive LNCaP and PC-3 human prostate cancer cells. 24 The ART-induced loss of AR prevented the cell proliferation and ablated total AR transcriptional activity, in which PI3K (phosphoinositide 3kinase)/Akt-1 signaling played an important role. Thus, the potential of AR-targeted prostate cancer chemotherapy was suggested for ART (Figure 2).…”
Section: ■ Sesquiterpene Lactonesmentioning
confidence: 99%
“…ART prevented Helicobacter pylori -induced gastric carcinogenesis via inhibition of nuclear factor kappa B (NF-κB) signaling . Interestingly, ART was found to enhance significantly the cytolytic activity of natural killer (NK) cells and the antitumor immune response in 4T1 breast cancer cells. , It selectively induced the ubiquitin-26S proteasome-mediated degradation of androgen receptor (AR) without altering receptor transcript levels in androgen-responsive LNCaP and PC-3 human prostate cancer cells . The ART-induced loss of AR prevented the cell proliferation and ablated total AR transcriptional activity, in which PI3K (phosphoinositide 3-kinase)/Akt-1 signaling played an important role.…”
Section: Sesquiterpene Lactonesmentioning
confidence: 99%